Analisis Beban Kerja dan Kebutuhan Tenaga Kerja pada lini Produksi Lemari Kaca dengan Pendekatan Work Load Analysis (WLA) - Alvianto, Deny Nur; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The increasing demand for glass cabinets at CV. Nanda Jaya has intensified the workload on the production line, leading to inefficiencies such as delays in order completion and potential worker fatigue. This study aims to analyze workload and determine the optimal number of workers at each workstation using the Work-Load Analysis (WLA) method. Data collection was conducted through direct observation, work-time measurement, heart rate monitoring using the Heart Rate Reserve (HRR) method, and uniformity and adequacy tests. The results indicate an imbalance in workload distribution, with the assembly station recording the highest standard time of 126.60 seconds, making it the primary bottleneck in the production process.